Ameliorative Effect of Surface Proteins of Probiotic Lactobacilli in Colitis Mouse Models - Chandhni, P. R.; Pradhan, Diwas; Sowmya, Kandukuri; Gupta, Sunny; Kadyan, Saurabh; Choudhary, Ritu; Gupta, Archita; Gulati, Ganga; Mallappa, Rashmi Hogarehalli; Kaushik, Jai K.; Grover, Sunita (Frontiers in Microbiology, 2021)
The increase in concern from viable cells of probiotics specifically in acute inflammatory conditions has led to the emergence of postbiotics conceptas a safer alternative therapy in the field of health and wellness. The aim of the present study was to evaluate the efficacy of surface proteins from three probiotic strains in dextran sodium sulphate and trinitrobenzenesulphonic acid induced colitis mouse models. The molecular weight of total surface proteins extracted from the three probiotic strains ranged from ~25 to ~250 kDa with the presence of negligible levels of endotoxins. S-layer proteins (SLPs) (~45 kDa) were found to be present only in the L. acidophilus NCFM strain. In the in-vivo study, significant differences were not observedin the weight loss and general appetite however the decrease in colon length was apparent in TNBS colitis control mice. Further, the administration of these surface proteins significantly reversed the histopathological damages induced by the colitogens and improved the overall histological score. The oral ingestion of these surface proteins also led to a decrease in myeloperoxidase activity and TNF-α expression while the IL-10 levels significantly increased for the strain NCFM followed by MTCC 5690 and MTCC 5689. Overall, the present study signifies the ameliorative role of probiotic surface proteins in colitis mice, thereby, offering a potential and safer alternative for the management of inflammatory bowel disorders.